OPTIMALISASI PENDAFTARAN TANAH OLEH BADAN PERTANAHAN NASIONAL KABUPATEN PANGKAJENE DAN KEPULAUAN PERSPEKTIF MAQASYID AL-SYARIAH - Herman, Muhammad Akbar; Tenripadang, Andi; Aisyah, Nur (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2023)
The guarantee of legal certainty of land rights has encountered various challenges, including in the implementation of land registration. The Badan Pertanahan Nasional has a central role in realizing systematic land registration despite the complexity of the problems that come with it. This study aims to determine the role of the Badan Pertanahan Nasional in optimizing land registration in Pangkajene dan Kepulauan Districts. The type of research used is qualitative field research with a normative juridical approach. The results showed that the stages of implementing land registration include the collection and processing of physical data, the collection and processing of juridical data and the issuance of documents proving proof of rights. Optimization of land registration in Pankajene dan Kepulauan Districts is carried out through several strategies, namely: a) responsive, fast and systematic services; b) systematic land program (free land registration), and c) online services. Registration of land rights is part of ijtihad to safeguard property and this effort is in line with one of the principles of al-Maqasid al-Sharia i.e. maintaining property (hifz al-mal) hifz al-mal).